Science in José Martí - José Ramón Gómez Cobelo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The José Martí´s look at the nineteenth century science enlivened the science of those times and motivates the XXI century researchers to conduct rational research from the perspective of the relationship philosophy, a term emphasized by the Master himself and of great value in systematic inquiry. In this article an analysis is made, based on the system approach and the relation philosophy of the Marti´s ideas on science, as well as the relation evolution from Marti´s perspective and its usefulness in the current time.